On the algebraic connectivity of some token graphs - Dalfó, C.; Fiol, M. A. (Journal of algebraic combinatorics, 2024)
The k -token graph F k ( G ) of a graph G is the graph whose vertices are the k -subsets of vertices from G , two of which are adjacent whenever their symmetric difference is a pair of adjacent vertices in G . It was proved that the algebraic connectivity of F k ( G ) equals the algebraic connectivity of G with a proof using random walks and interchange of processes on a weighted graph. However, no algebraic or combinatorial proof is known, and it would be a hit in the area. In this paper, we algebraically prove that the algebraic connectivity of F k ( G ) equals the one of G for new infinite families of graphs, such as trees, some graphs with hanging trees, and graphs with minimum degree large enough. Some examples of these families are the following: the cocktail party graph, the complement graph of a cycle, and the complete multipartite graph.